Pengaruh Budaya Sekolah dan Pembelajaran Geografi Terhadap Pembentukan Karakter Peduli Lingkungan Siswa - Lili Asriyani; Ramli Umar; Maddatuang Maddatuang (Jurnal Penelitian Pendidikan Geografi, 2025)
Makassar is the fifth largest metropolitan city in Indonesia. This status makes the movement of life in it very dynamic. However, behind its great appeal, Makassar City has a number of environmental problems such as garbage, flooding, groundwater decline, and air pollution. One important step that needs to be taken to overcome increasingly serious environmental problems is to foster an attitude of environmental concern in students. This study aims to analyze the influence of school culture and geography learning on the formation of students' environmental awareness character. The method used is a survey with a quantitative approach. Data were analyzed using multiple linear regression. The results showed that environmental content in school culture was in the moderate category (54%), environmental content in Geography learning was in the high category (75%), and the level of students' environmental awareness was at the caring level (82%). The influence of school culture on the formation of environmental awareness character has an R² value of 0.177 (17.7%), while Geography learning has an influence of 0.082 (8.2%). Together, school culture and Geography learning influence students' environmental awareness character with R² of 0.180 (18.0%).